HUBUNGAN PARITAS DENGAN BERAT BAYI LAHIR DI RUMAH SAKIT UMUM DAERAH DR. WAHIDIN SUDIRO HUSODO MOJOKERTO - Saudah, Noer; Wahyu Novitasari, Widya (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Maternal Mortality Rate and Infant Mortality Rate is indicator of the succes of development in the health. Infant is one indicator that a healthy newborn. There are many factors that effect, among parity. The purpose of this research is determine the relationship between parity and infant’s birth weight. Research used analytic correlation design. The population were 128 respondents in a public hospital dr. Wahidin Sudiro Husodo since April to June 2015. Samples technic was non probability sampling (total sampling). Independent variable was parity and dependent variable was infant’s birth weight. Data taken by retrospective data observasion patient’s medical records. The results of the crosstabulation used frequency distribution in spss 1.6 for windows parity with multiparity gave birth babies with low birth weight were 61 (76,3%), parity with primiparity gave birth babies with normal birth weight were 35 (74,5%) and parity with grandemultiparity gave birth babies with normal birth weight were 1 (0,8%). This research used statistical test spearman rho test and result showed p = 0,00 <0,05 the H0 was rejected, which means there was a relationship between parity and infant’s birth weight. Antenatal care can detected the risk of Low Birth Weight.Keywords: Infant’s Birth Weight, Parity.